Reduced radioiodine uptake at increased iodine intake and 131I-induced release of “cold” iodine stored in the thyroid - Meller, B.; Haase, A.; Seyfarth, M.; Wenzel, B. E.; Richter, E.; Baehre, M. (Nuklearmedizin - NuclearMedicine, 2005)
Aim: The extent of urinary iodine excretion (UIE) provides information about iodine supply and release. In the present study we investigated correlations between UIE and radioiodine uptake (RIU) as well as effects of radioiodine therapy on UIE in patients with autonomous goitre. Patients, methods: In 197 consecutive patients with thyroid autonomy, UIE was measured twice during radioiodine test (RITe) and correlated with RIU. In 98 of these patients, thyroglobulin and thyroid volume (V) were determined prior to therapy. Individual changes in urinary iodine excretion (ΔUIE) and TG (ΔTG) could be investigated four weeks (4W) and six months (6M) after radioiodine therapy. Additionally, ΔV was determined 6M after therapy. ΔUIE, ΔTG and ΔV were correlated with target dose and target volume. Results: Patients with higher iodine excretion exhibited significantly lower thyroidal radioiodine uptake values. Twofold increased UIE prior to therapy decreased radioiodine uptake by 25%. Compared with pretherapeutic values, UIE and TG were significantly increased four weeks after radioiodine therapy (p <0.001). Median values of both parameters were found to be doubled. The product of target dose and target volume was not only correlated with a decrease of thyroid volume 6M after therapy, but also with an increase of UIE and TG in the early phase after therapy. Conclusions: It was confirmed that UIE during RITe is a measure for iodine intake and can be used to investigate the competition between stable iodine and radioiodine. The increase of UIE and TG four weeks after therapeutic administration of radioiodine can be explained by disintegrated thyroid follicles. The therapy-induced iodine release may be one important cause for the development of hyperthyroidism in some patients during the first weeks after radioiodine therapy. It may contribute to the known decrease of radioiodine uptake after preapplications of 131I in various thyroid diseases.
Keywords: Radioiodine therapy; urinary iodine excretion; thyroglobulin